Comparison of Aerodynamic, Bowen-Ratio, and Penman-Monteith Methods in Estimating Evapotranspiration of Oil Palm Plantation - Tania June; Ni Wayan Srimani Puspa Dewi; Ana Meijide (Agromet, 2018)
Oil palm is one important agricultural commodity that has high economic value. Oil palm productivity is significantly influenced by its water use (needs). Measurement and estimation of oil palm evapotranspiration is needed for determination of its water needs. Various methods are available and this study compare three methods, consisting of aerodynamic, Bowen-Ratio and Penman-Monteith methods in analyzing water needs/use of oil palms plantation located in PTPN VI Jambi.  Peak of evapotranspiration rate occured in the afternoon around 13.00 and 14.00 local time. Bowen-Ratio method has higher estimation value of evapotranspiration than the other two methods. Ratio between evapotranspiration and global radiation of two and ten-years old oil palm plantations remain similar, around 47%. Penman Monteith method has the nearest estimation value to reference method (aerodynamic method) showed by the smallest RMSE value, 0.087 for two years oil palm and 0.157 for ten-years old oil palm.